Pelatihan Dan Pendampingan Evaluasi Website Menggunakan Sortsite 5.3.5 Pada Website “Mal Pelayanan Publik” Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Samarinda - Bambang Irawan; Muhammad Nizar Hidayat; Axel Prasetyo Sudiro; Hendra Wibowo Hului (Universitas Lancang Kuning, 2022)
The use of the website as a means to bring public services closer to the community is indeed a must for the government in the digital era. The website plays an important role as a medium for the government to disseminate public information. Therefore, government websites that are built and funded through public funds must be able to reach all levels of society and have good performance. Based on that, this Community Service Program seeks to make a small contribution to the Samarinda City Government, especially the Samarinda City DPMPTSP related to training and assistance in evaluating the Public Service Mall website using SortSite 5.3.5. The implementation of the Community Service Program starts from the stages of problem identification, verification, provision of materials, implementation of training and mentoring and evaluation of activities. Based on the observation, it can be said that the training and mentoring program has successfully increase the skill and knowledge of DPMPTSP website operator. Keywords: Training, Mentoring, Website Evaluation, Samarinda City DPMPTS